On oscillation of a food-limited population model with time delay - Leonid Berezansky; Elena Braverman (Abstract and Applied Analysis)
For a scalar nonlinear delay differential equation Ṅ(t) = r(t)N(t)(K − N(h(t)))/(K + s(t)N(g(t))),r(t) ≥ 0, h(t) ≤ t, g(t) ≤ t and some generalizations of this equation, we establish explicit oscillation and nonoscillation conditions. Coefficient r(t) and delays are not assumed to be continuous.